1,2,4,5-Tetrakis(tetramethylguanidino)-3,6-diethynyl-benzenes: fluorescent probes, redox-active ligands and strong organic electron donors - Wagner, Conrad; Kreis, Franka; Popp, Dennis; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2020)
In this work, the change of reactivity induced by the introduction of two para-ethynyl substituents (CCSi(iPr)3 or CCH) to the organic electron-donor 1,2,4,5-tetrakis(tetramethylguanidino)-benzene is evaluated. The redox-properties and redox-state dependent fluorescence are evaluated, and dinuclear CuI and CuII complexes synthesized. The Lewis-acidic B(C6F5)3 substitutes the proton of the ethynyl −CCH groups to give new anionic −CCB(C6F5)3− substituents, leading eventually to a novel dianionic strong electron donor in its diprotonated form. Its two-electron oxidation with dioxygen in the presence of a copper catalyst yields the first redox-active guanidine that is neutral (instead of cationic) in its oxidized form.
First published: 05 May 2020
Gesehen am 10.11.2021